Synthesis, Characterization, and Biological Activity of N1-Methyl-2-(1H-1, 2, 3-Benzotriazol-1-y1)-3-Oxobutan- ethioamide Complexes with Some Divalent Metal (II) Ions. (21st November 2007) - Al-Awadi, Nouria A.; Shuaib, Nadia M.; Abbas, Alaa; El-Sherif, Ahmed A.; El-Dissouky, Ali; Al-Saleh, Esmaeil
Abstract : A new series ofZn 2 +, Cu 2 +, Ni 2 +, andCo 2 + complexes ofN 1 -methyl-2-(1 H -1, 2, 3-benzotriazol-1-yl)-3-oxobutanethioamide (MBOBT), HL, has been synthesized and characterized by different spectral and magnetic measurements and elemental analysis. IR spectral data indicates that (MBOBT) exists only in the thione form in the solid state while 13C NMR spectrum indicates its existence in thione and thiole tautomeric forms. The IR spectra of all complexes indicate that (MBOBT) acts as a monobasic bidentate ligand coordinating to the metal(II) ions via the keto-oxygen and thiolato-sulphur atoms. The electronic spectral studies showed that (MBOBT) bonded to all metal ions through sulphur and nitrogen atoms based on the positions and intensity of their charge transfer bands. Furthermore, the spectra reflect four coordinate tetrahedral zinc(II), tetragonally distorted copper(II), square planar nickel(II), and cobalt(II) complexes. Thermal decomposition study of the complexes was monitored by TG and DTG analyses underN 2 atmosphere. The decomposition course and steps were analyzed and the activation parameters of the nonisothermal decomposition are determined. The isolated metal chelates have been screened for their antimicrobial activities and the findings have been reported and discussed in relation to their structures.